Pendekatan Tasawuf Dalam Dakwah: Menyeimbangkan Dimensi Jasmani Dan Rohani Di Era Modern - Elfiyatul Afifah, Diana (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
The increasing complexity of modern life, particularly in the digital era, poses significant challenges to maintaining a holistic balance between physical and spiritual well-being among Muslim communities. Traditional da'wah approaches often emphasize ritual and doctrinal practices, neglecting the integrative needs of both bodily health and inner spirituality. This study addresses this gap by investigating the implementation of a Sufi-inspired approach to da'wah that harmonizes the jasmani (physical) and rohani (spiritual) dimensions to meet contemporary demands. Employing a qualitative research methodology grounded in literature review and case study analysis, this research explores how modern Sufi teachings and digital media platforms facilitate comprehensive spiritual development and social empowerment. The findings reveal that integrating physical practices such as healthy lifestyle promotion and mindfulness meditation with spiritual exercises like dhikr creates measurable improvements in community psychological well-being and social cohesion. Additionally, the adoption of digital applications and virtual communities expands the reach and personalization of spiritual guidance, fostering sustained engagement in both physical and spiritual health. This fusion of classical Sufi wisdom with modern methods marks a novel paradigm in Islamic da'wah, referred to as “social tasawwuf,” which supports holistic human development and addresses challenges such as social alienation, identity erosion, and spiritual fragmentation. The research concludes that contemporary da'wah strategies must incorporate this holistic model to remain relevant and impactful. Future research should focus on empirical assessments of digital tasawwuf interventions and explore frameworks for integrating these models systematically into broader religious education and community development.